Methane conversion over artificial photocatalysts - Lin, Xiang-Yu; Li, Jing-Yu; Qi, Ming-Yu; Tang, Zi-Rong; Xu, Yi-Jun (Catalysis communications, 2021)
Methane conversion into value-added chemicals such as alkanes, alcohols and other hydrocarbons represents an enduring attractive yet challenging topic in response to the global energy and environment crisis. Conventional thermocatalytic methane conversion suffers from harsh reaction conditions and intense energy consumption to push forward such transformation. In contrast, photocatalytic technology, featuring clean energy input, low energy consumption and unique reaction route, has shined light on the road to the conversion of methane. In this review, we present a concise overview of the typical photocatalytic processes for methane conversion over artificial photocatalysts, mainly including the non-oxidative coupling of methane (NOCM), the methane dry gas reforming (MDR), the partial oxidation of methane (POM) and methylation reaction. In particular, we discuss their performance in different reaction systems from the aspects of reaction mechanisms and catalyst design, aiming to acquire in-depth understanding of the light-driven methane conversion. Finally, the current challenges and future perspectives in this promising frontier of photocatalytic methane conversion are presented. [Display omitted] •Photocatalysis has emerged as a promising way for the greener usage of methane.•Advances of methane conversion over artificial photocatalysts has been reviewed.•The dilemma and future of photocatalytic methane conversion are prospected.